MR histology of advanced atherosclerotic lesions of ApoE- knockout mice. (January 2016) - Naumova, A; Yarnykh, V; Ferguson, M; Rosenfeld, M; Yuan, C
Abstract: The purposes of this study were to examine the feasibility of determining the composition of advanced atherosclerotic plaques in fixed ApoE-knockout mice and to develop a time-efficient microimaging protocol for MR histological imaging on mice. Five formalin-fixed transgenic ApoE-knockout mice were imaged at the 9.4T Bruker BioSpec MR scanner using 3D spoiled gradient-echo sequence with an isotropic field of view of 24 mm 3 ; TR 20.8 ms; TE 2.6 ms; flip angle 20°, resulted voxel size 47 × 63 × 94 pm 3 . MRI examination has shown that advanced atherosclerotic lesions of aorta, innominate and carotid arteries in ApoE-knockout mice are characterized by high calcification and presence of the large fibrofatty nodules. MRI quantification of atherosclerotic lesion components corresponded to histological assessment of plaque composition with a correlation coefficient of 0.98.